Pectic Acid Lyases of Bacillus polymyxa - Nagel, C. W. (1970)
Four enzymes were separated from an extracellular preparation of Bacillus polymyxa by carboxymethylcellulose column chromatography. The pH optima were 8.3 to 8.5, 8.7 to 8.9, 9.2 to 9.4, and 9.5 to 9.6. All of the enzymes required calcium ion for maximum activity, whereas strontium ion was only partially effective in stimulating activity. Cobalt was the only other cation tested which was effective in two of the enzymes. The lyases seem to attack a calcium salt-bridged substrate. K(m) and V(m) data of the four enzymes on various oligomers are presented as well as paper chromatographic evidence of preferred sites of attack. All of the enzymes are endo-enzymes which, based upon their characteristics, were classed into two types.